Implementasi Deteksi Perkembangan Anak Melalui Pelatihan KPSP ( Kuesioner Pra Skrining Perkembangan) pada Guru TK Islam Nurul Izzah - Haryani, Siti; Astuti, Ana Puji; Minardo, Joyo; Sari, Kartika (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2022)
Development is an increase in abilities (skills) in more complex body structures and functions in a regular and predictable pattern, as a result of the maturation process. The purpose of this activity is to provide an overview of the detection of child development through training. The method used is to provide KPSP training (Pre-Development Screening Questionnaire) to teachers at Nurul Izzah Kindergarten in order to detect the development of students according to their age. The result of this activity is that 100% of teachers participate in developmental detection training using KPSP and the development of students who are carried out for developmental detection is in accordance with their age(100%).ABSTRAKPerkembangan merupakan bertambahnya kemampuan (skill) dalam struktur dan fungsi tubuh yang lebih kompleks dalam pola yang teratur dan dapat diramalkan, sebagai hasil dari proses pematangan. Tujuan dari kegiatan ini adalah memberikan gambaran tentang deteksi perkembangan anak melalui pelatihan. Metode yang digunakan yaitu memberikan pelatihan KPSP (Kuesioner pra Skrining Perkembangan) kepada para guru di TK Nurul Izzah agar dapat mendeteksi perkembangan para siswa sesuai usianya. Hasil kegaiatan ini adalah 100 % guru mengikuti pelatihan deteksi perkembangan dengan menggunakan KPSP dan perkembangan siswa yang dilakukan deteksi perkembangan sudah sesuai dengan usianya (100%).